Promising Examples from Outside Wisconsin - (:unkn) unknown (My University, 2009)
The fall 2009 forum, hosted by the Wisconsin Center for the Advancement of Postsecondary Education (WISCAPE) on the University of Wisconsin?Madison campus, will bring together policymakers, practitioners, students, scholars, and the public to discuss the current state of student financial aid in Wisconsin and the implications of the state?s changing student and workforce demographics. The forum?s objective is to include a wide array of participants in an effort to broaden the understanding of available financial aid, foster discussion about the future of need-based aid in Wisconsin, and craft policy recommendations aimed at increasing postsecondary access and success throughout the state. WISCAPE will produce a summary document based on forum discussions and distribute the publication widely to spur an on-going, state-wide discussion about the needs of the Wisconsin?s postsecondary students?traditional, returning adult, and otherwise.
Keywords: Finance and Economics; Access, Persistence, and Success